How Do Primary Care Physicians Perceive the Role of Nurses in Quality Measurement and Improvement? The Israeli Story - Nissanholtz-Gannot, Rachel; Goldman, Dorit; Rosen, Bruce; Kay, Calanit; Wilf-Miron, Rachel (Frontiers in Public Health, 2016)
Background: Israel has boasted a highly effective national quality-monitoring programme for community-based health services since 2004. The programme involves ongoing monitoring of the quality of selected services provided by Israeli health plans and includes approximately 70 indicators. Objective: To analyse Israeli primary care physicians’ (PCPs’) perceptions of nurses’ roles in the national quality-monitoring programme and their contribution to improving healthcare quality. Design: A cross sectional survey using self-reported questionnaire. Setting: Four Israeli health plans, covering 100% of the Israeli population. Participants: A representative sample of 1,000 Israeli PCPs. Response rate of 69% (605 of the 884 physicians who met the study criteria). Methods: A questionnaire combined with closed questions on the attitudes and behaviours of the physicians regarding nurses’ involvement in quality monitoring and open questions about the changes that had made in their practice as a result of the quality monitoring programme. Results: Most respondents (74%) agreed that nurses contribute to practice quality and share responsibility for improving quality measures. Physicians who felt that quality monitoring improved the quality of care and those who supported the programme were more likely to consider that nurses shared responsibility for the quality of care. However, in open ended-questions about the changes they made in their practices as a result of the programme, they made minimal reference to the importance of nurses and their contribution to improved quality indicators. Conclusions: There was a disparity between the closed-ended and open-ended questions regarding the way physicians depicted the role of nurses in quality monitoring and improvement. This disparity may be due to the fact that physicians do not yet fully appreciate the growing involvement of nurses in these areas